Perubahan Pola Pikir Masyarakat Melalui Program Bak Sampah di Dusun 2, Desa Cikembulan, Kecamatan Kadungora, Kabupaten Garut - Ramadhani, Daffa; Prasetya, GIlang; Kennori, Dimas; Arsi, Novi; Novita, Marisa (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The problem of waste being dumped into rivers remains a serious environmental issue in Cikembulan Village, Kadungora District, Garut Regency. Lack of public awareness in waste management is the main cause of environmental pollution. Through the UNLA KKNM Group 20 Program, students collaborated with the community of Dusun 2 RW 10 to create the “Waste Incineration Bin” program as a solution to change the community's mindset from the habit of disposing waste into rivers. The program implemented by the UNLA KKNM Group 20 students aims to educate the community about the importance of waste sorting, the use of organic waste as compost for rice fields, and controlled burning for non-recyclable residual waste. The results of this activity show an increase in community awareness of the importance of maintaining environmental cleanliness, as well as a reduction in the volume of waste disposed of in the river. The Waste Incineration Bin Program demonstrates that changes in community behavior can be achieved through a participatory and educational approach that is sustainable.